SEMIOTIK MAKNA PADA WACANA NGEMBAH BELO SELAMBAR ADAT KARO LANGKAT (KAJIAN SEMIOTIKA SOSIAL) - Beru Ginting, Sri Ulina (Universitas Negeri Surabaya, 2017)
Ngembah Belo Selambar is one of the rituals of marriage of girls according to Karo custom. The purpose is to get the willingness of girl, parents, sembuyak, Anak Beru, Kalimbubu Singalo Bere-bere and kalimbubu Singalo perkempun on the proposal. Initially the event Ngembah Belo Selambar is done at night after finished eating. However, nowadays events are sometimes held at noon or afternoon, which begins or ends by eating together. Studying it through the social semiotics of the implementation of Ngembah Belo Selambar has a semiotic meaning of custom equipment used from Amak Mentar Kehamaten (Honest White mat), Khamas Kehamaten, Luah (gifts) as cimpa unung unung bulung singkut (lepat pulut wrapped wear palm leaves), side dishes of chicken, Uis pudun pensih can be tried with money, Ose (clothes), all this equipment has a very wide meaning as a symbol in the Karo Langkat tribe. This article looks for meaning not according to the researchers themselves, but the meaning in accordance with what is expressed by the speakers. Researchers look for the quality of the semiotic meaning of verbal and nonverbal symbols based on the quality of the content, the usage of the symbolic meaning that most appear in the marriage of lexical or grammatical meaning, meaning based on social context. The research method used is descriptive analysis method, where will be made a systematic and accurate description of the data under study. Descriptive method was chosen because of research done to see clearly about the object under study naturally. Form Symbol/semiotic sign lays on the discourse Ngembah Belo Selambar and Semiotik Meaning on Equipment discourse Ngembah Belo Selambar.